Consumer Psychology of Tourism, Hospitality and Leisure 2004
DOI: 10.1079/9780851997490.0227
|View full text |Cite
|
Sign up to set email alerts
|

The role of expressive and instrumental factors in measuring visitor satisfaction.

Abstract: This study describes overall visitor satisfaction as a function of instrumental and expressive factors using data obtained from a panel of 409 households in Virginia, West Virginia, North Carolina, Maryland, and washington, District of Columbia, USA, in the summer of 2002. Its objective is accomplished by testing whether instrumental and expressive attributes are distinct behavioural indicators that could better predict visitor satisfaction. It also tests whether visitor types based on motivation for travel mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Therefore, the main elements of satisfaction, the expressive and instrumental attributes in tourism settings, can be examined within the context of tourism system representing two major components of the market place, namely, demand and supply. 59 A number of studies also have examined tourist motivation involved in travel and recreational activities. However, a limited number of tourism studies have addressed and examined the constructs of motivation and satisfaction in the same context.…”
Section: Satisfaction Destination Attributes and Motivationmentioning
confidence: 99%
“…Therefore, the main elements of satisfaction, the expressive and instrumental attributes in tourism settings, can be examined within the context of tourism system representing two major components of the market place, namely, demand and supply. 59 A number of studies also have examined tourist motivation involved in travel and recreational activities. However, a limited number of tourism studies have addressed and examined the constructs of motivation and satisfaction in the same context.…”
Section: Satisfaction Destination Attributes and Motivationmentioning
confidence: 99%
“…The literature on tourist motivation indicates that the examination of motivations based on the push and pull factors has been generally accepted (Uysal et al, 2004). Finding motivations of grandparents help tourism companies to plan their marketing and product development and allowing tourism marketers to allocate scarce tourism resources more efficiently as well.…”
Section: Motivationmentioning
confidence: 99%
“…Seubsamarn (2009) found that the correlation between overall satisfaction and two underlying motivation factors (Familiarity/ Relaxing/Trip plans and Unfamiliarity/Adventure) was positive and significant. Uysal and Williams (2004) also have examined a model by testing tourist satisfaction in respect of tourist type based on travel motivation and attributes of destination and discovered that the relationship between satisfactions and attribute factors were moderate. This result was also similar with Huh (2002) where the relationship between overall satisfaction and the selected cultural/heritage attributes were moderate.…”
Section: Research Hypothesismentioning
confidence: 99%